Penerapan Nilai-Nilai Positif Olahraga Dalam Interaksi Sosial Antar Siswa di SMA (Department of Physical Education, Sport, Health and Recreation, 2015)
The research problem of this study is how to applicant the positive values of sport in social interactions whichoccur among high school students The goal is determining the extent to which students can apply the positivevalues inherent in sport on their social interactions in the Senior High School level education in the academicyear of 2014/2015 at Wonosobo regency.This research used quantitative research methodology and empowered by survey method.Application of research results positive values of sports in social interaction among students in Senior High School at Wonosobo regency which most of the students have been able to apply the values of honesty, cooperation, fair play, responsibility, fairness, tolerance, respect, leadership with good categories.The conclusion of this study, that the majority of high school students in Wonosobo district have been able to apply the positive values of sport in their social interactions in the school environment well.